KONSEP AWAL PEMBERDAYAAN MASYARAKAT OLEH ‘AISYIYAH - Adib Sofia (UIN Sunan Kalijaga, 2021)
One of the social capital that the Indonesian nation has to conduct community empowerment since the pre-independence era until today is ‘Aisyiyah. Since its establishment in 1917, ‘Aisyiyah has owned many models of social empowerment through its movements spread throughout Indonesia and abroad. ‘Aisyiyah has also conducted the community empowerment through a media, Suara ‘Aisyiyah. The initial concept of community empowerment by ‘Aisyiyah needs to be revealed because it is the basic identification conducted by ‘Aisyiyah as a whole until today. This writing reveals two things. First, the initial concept of community empowerment by ‘Aisyiyah contained in Suara ‘Aisyiyah in the era of national movement. Second, the community empowerment sectors conducted by Suara ‘Aisyiyah in the era of national movement. As a whole this writing reveals a phenomenon that is different from a description happening in the colonial era. Generally in the pre-independence era women were described as the members of society who were uneducated, backward, and had no actions in public domain. This writing reveals that women in the pre-independence era had the concept of community empowerment complete with its sectors